Teacher assistants in special education competency mapping - Marquez, Leila Rimando (2008)
A descriptive survey method was conducted to determine the core and auxiliary competencies that an effective teacher assistant must possess.There was a total of 78 respondents, 39 teacher assistants and 39 SPED teachers. Two sets of parallel questionnaires from 12 Department of Education accredited private SPED schools in Metro Manila were used. Factor analysis was employed. Findings revealed that the educational background of teacher assisstants in private SPED schools in Metro Manila is diverse, some have formal training while others do not have. The study has identified basic occupational/ work related knowledge, occupational/work related skills and personal characteristics that are significant for teacher assistants to possess. While teacher assistants are utilized only in private SPED schools at present, their hiring is recommended in public SPED schools in the future.